PENGARUH MODEL COOPERATIVE LEARNING) TERHADAP HASIL BELAJAR - Nurdiyanah; Ratika Novianti; Nur Widiastuti (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
The aim of this research is to determine the magnitude of the influence of the type cooperative learning model on the social studies learning outcomes results of data nalysis using SPSS 16.0 for Windows program calculations using t test analysis for samples originating from the distribution different Independent samples st, shows that the Sig value = 0.000 < 0.05. Thus the Sig value < α at the 5% significance level, then the hypothesis (Ha) accepted, with a large influence obtained from the percentage value of the determination coefficient/R Square (R2) of 0.201 x 100 = 20.1%. This means that "there is (is) and is a significant influence type cooperative learning model in the social studies learning outcomes.